The effect of temperature on denitrification kinetics and biological excess phosphorus removal in nutrient removal activated sludge systems in temperate climates (12°C - 20°C) - Pilson, Richard Adair (Water Research Group, 2016)
Filamentous bulking in nutrient (N & P) removal activated sludge systems is a problem of considerable magnitude - three quarters of 45 plants surveyed were found to have bulking sludges to the extent that sludge settleability (DSVI) was adversely affected. If filamentous organism proliferation could be controlled and thereby sludge settleability improved to below DSVI of 100 ml/g, then with provision for factors such as additional aeration capacity, between 50% and 7 5% more wastewater could be treated in existing nutrient removing activated sludge plants. Anoxic-aerobic (AA) or low F/M filaments appear to proliferate in activated sludge plants that incorporate biological nitrogen removal. From earlier research, Casey et al. (1992a) showed that the cause for AA filament proliferation lay in the denitrification behaviour of the N removal systems. They hypothesized that filamentous and floe-forming organisms have different denitrification behaviour - the former reducing nitrate only as far as nitrite whereas the latter reducing nitrate all the way to nitrogen gas via the denitrification intermediates nitrite, nitric oxide (NO) and nitrous oxide (N₂O). If nitrate and nitrite removal to nitrogen gas is not complete in the anoxic reactor, then, when conditions become aerobic, the accumulated denitrification intermediates, in particular NO, inhibit oxygen uptake in the floc-formers. The filaments do not experience this inhibition because by reducing nitrate only to nitrite, no denitrification intermediates accumulate in their cytoplasmic membrane and consequently they can successfully compete against the floe-formers and proliferate in the N removal systems. If denitrification is complete, no residual intracellular denitrification intermediates remain in the floc-formers. Therefore, when conditions become aerobic, the floc-formers are not inhibited in their oxygen uptake and can successfully compete against the filamentous organisms which cause the bulking.